Trends, challenges and solutions of digital information security in Central and Eastern Europe - Serhii Lubenets; Igor Harchenko; Tetiana Shediakova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
The problems and directions of ensuring effective international digital information security in Central and Eastern Europe (CEE) are considered, which are based on the analysis of the current state, key trends and challenges of information security in this region, using current reporting materials of international companies specializing in information security issues and development of appropriate complex tools for its provision. The subject of research in the article is the issue of ensuring international digital information security in the CEE. The goal is to study the current state, current problems and trends of international digital information security on the example of the region of Central and Eastern Europe in order to find ways to improve its effectiveness. Task: to process and analyze current reporting related to the current state of international digital information security in the CEE region; to explore the key trends, challenges, problems and industry specificities of digital information security in CEE; analyze approaches to assessing the current state of information security of international organizations in the CEE region and directions for its improvement. The general scientific method of system analysis is used - to determine the current state, key trends and challenges of digital information security, as well as to research promising directions for improving its effectiveness. The following results were obtained: based on the processing of reports concerning the current state of international digital information security in Central and Eastern Europe, key trends, challenges and problems of digital information security in the CEE region were investigated. The sectoral features of digital information security in the spheres of financial services, production and retail trade of this region have been determined. Effective approaches to assessing the current state of information security of international organizations in the CEE have been analyzed. Possible directions for its improvement and prospects for further scientific research on this topic are determined. Conclusions: the obtained results made it possible to understand the current landscape of cyber security in Central and Eastern Europe in general. Positive impulses have been identified in the focus of companies in the region on strengthening cyber security, which requires them to have a clear orientation in the information risk management system. The biggest current problems of CEE cyber security are highlighted. It has been established that the existing concern and actual behavior regarding information security in CEE contradict each other: most international companies have a significant dissonance between the fears of information threats and the actions of their management. It was determined that one of the biggest problems of CEE organizations in ensuring information security is the low level of involvement of their managers in this process, as well as the neglect of the awareness of the employees of the organizations about security and cyber protection. Establishing a secure remote work environment remains a top priority, along with the ongoing fight against malicious malware attacks. It was determined that the use of cloud technologies remains particularly relevant for international companies and CEE institutions. The need for cooperation between organizations and external suppliers of relevant solutions in ensuring the information security of the region was revealed. It has been established that there are some unique points regarding information security issues in the industry comparison; financial services, manufacturing and retail trade stand out among such CEE special industries. An effective list of control questions regarding an adequate assessment of the current state of the organization's information security to determine potential directions for its improvement is proposed. Plans for improving the effectiveness of digital information security of organizations in the CEE region are outlined.